Activation of the sintering process of iron powders by introducing nanodispersed additives - Matrenin S. V.; Ilyin A. P. Aleksandr Petrovich; Slosman A. I.; Tolbanova L. O. Lyudmila Olegovna (2009, 2009)
The results of studying of the effect of additions on nanodispersed iron powder (Fe-NP) obtained by the electrical explosion method on the formation and sintering of industrial coarse-grain iron powder are presented. The effect of amount of Fe-NP added to the charge material on compactibility and moldability of compacts, properties, microstructure, and phase composition of sintered material is analyzed. Electrically explosive Fe-NP is shown to be low-technologic. Charges based on the coarse-grained iron powder that contain up to 20% Fe-NP have good compactibility and moldability. It is established that introduction of Fe-NP into the charge causes activation of sintering and is favorable for obtaining the sintered samples with fine-grain crystalline structure and increased physicomechanical characteristics. The effect of amount of the Fe-NP addition to effective activation energy of sintering is evaluated.